A bioinformatic approach to characterize the vitellogenin receptor and the low density lipoprotein receptor superfamily in the newt Cynops orientalis - Chiara Spinsante; Federica Carducci; Elisa Carotti; Adriana Canapa; Davide Bizzaro; Maria Assunta Biscotti; Marco Barucca (Scientific Reports)
Abstract The Low Density Lipoprotein receptors (LDLRs) gene family includes 15 receptors: very low-density lipoprotein receptor (VLDLR), LDLR, Sorting-related receptor with A-type repeats (SORLA), and 12 LDL receptor-related proteins (LRPs): LRP1, LRP1B, LRP2, LRP3, LRP4, LRP5, LRP6, LRP8, LRP10, LRP11, LRP12, LRP13. Most of these are involved in the transduction of key signals during embryonic development and in the regulation of cholesterol homeostasis. In oviparous animals, the VLDL receptor is also known as VTGR since it facilitates the uptake of vitellogenin in ovary. In tetrapods, information concerning genes encoding these proteins is limited to a few taxa. Here, we report the characterization of VTGR in the amphibian Cynops orientalis. The secondary structure analyses and the expression profiles obtained from hepatic and gonadal tissues of C. orientalis supported the role of VTGR as vitellogenin oocyte membrane receptor in this species. Moreover, to get a holistic view of the evolutionary history of this gene superfamily, we extended our investigation to all 15 genes belonging to the LDLR superfamily analyzing through a phylogenetic analysis a total of 161 sequences belonging to 11 genera of vertebrates. The position of LRP8 in the tree and its expression findings in C. orientalis ovary allowed us to suggest that other proteins of the LDLR superfamily could act as receptors during vitellogenesis.